Nursing experience of auricular acupoint combined with manipulative therapy for a patient with hypertension before operation of mixed hemorrhoid (耳穴联合手法治疗混合痔术前并发高血压病1例的护理体会) - DONG Yuxia (董玉霞); E haiyan (鄂海燕); QIN Shasha (秦沙沙); XU Jingjin (徐京巾); WEI Yongchun (魏永春); LI Ye (李野); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the nursing experience of auricular acupoint combined with manipulative therapy for a patient with mixed hemorrhoids combined with hypertension. Nursing measures included nursing assessment, auricular acupoint massage, ear tip bloodletting method and auricular acupoint sticking method. The patient blood pressure was under control and head pain was relieved after intervention. The combined auricular acupoint therapy has advantages of easy-to-use operation, less adverse reactions and high degree of patient acceptance. (本文总结1例混合痔术前合并高血压病患者运用耳穴联合疗法的护理经验, 包括护理评估、耳穴按摩、耳尖放血及耳穴贴压操作方法。通过实施耳穴联合疗法, 患者血压得到控制, 头痛缓解。耳穴联合疗法操作简单、不良反应少, 患者易于接受。)